2021
DOI: 10.1186/s42269-021-00578-y
|View full text |Cite
|
Sign up to set email alerts
|

Response of sweet pepper plants to foliar application of compost tea and dry yeast under soilless conditions

Abstract: Background Sweet pepper is considered one of the most important vegetable crops cultivated for local consumption and exportation. Under greenhouse conditions, the effects of different rates of yeast and compost tea on vegetative growth, leaves mineral content, fruit yield and quality were studied for two consecutive years 2018/2019 and 2019/2020 under soilless conditions. Nine treatments of compost tea (CT) and or dry yeast (DY) were applied using control (sprayed with distilled water); CT (10L… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…The results show in Table (1) that the foliar treatment of NanoNPK2 at a concentration of (15%) was excelled in its counterparts in producing the highest mean of plant height (58.45 and 57.54 cm), the number of main stems of the plant (4.03 and 3.94 stems) and the number of leaves per plant (56.34 and 53.63 leaf) for both seasons, respectively compared to C50%, which produce the lowest values for the same traits (46.83, 44.37 cm plant -1 and 2.90, 2.87 stem plant -1 and 41.15, 40.46 leaf plant -1 for both seasons, respectively). The NanoNPK2 treatment was significantly superior in producing the highest leaf content of total chlorophyll, which reached 504.4 and 486.3 mg 100g F.W.…”
Section: Results and Discussion Vegetative Growth Traitsmentioning
confidence: 99%
“…The results show in Table (1) that the foliar treatment of NanoNPK2 at a concentration of (15%) was excelled in its counterparts in producing the highest mean of plant height (58.45 and 57.54 cm), the number of main stems of the plant (4.03 and 3.94 stems) and the number of leaves per plant (56.34 and 53.63 leaf) for both seasons, respectively compared to C50%, which produce the lowest values for the same traits (46.83, 44.37 cm plant -1 and 2.90, 2.87 stem plant -1 and 41.15, 40.46 leaf plant -1 for both seasons, respectively). The NanoNPK2 treatment was significantly superior in producing the highest leaf content of total chlorophyll, which reached 504.4 and 486.3 mg 100g F.W.…”
Section: Results and Discussion Vegetative Growth Traitsmentioning
confidence: 99%
“…These results are consistent with previous studies. For instance, [8] found that a combination of tea fertilizer and dry yeast significantly increased the height of sweet pepper plants. Similarly, [12] and [7] reported that organic fertilizers have a positive effect on the height of chili pepper plants.…”
Section: Plant Heightmentioning
confidence: 99%
“…There are many studies mentioned that the addition of organic fertilizer with inorganic fertilizer increased the growth and productivity of chili pepper. The result of studies also showed that the mixture of compost tea and dry yeast used in fertilizing sweet pepper led to a significant increase in vegetative growth, quality of fruits (height, diameter and fresh weight), total yield, leaf mineral content (N, P, and K) and fruit content of nutritional value (calcium), and vitamin C [8].…”
Section: Introductionmentioning
confidence: 97%
“…YE serves as an economical biofertilizer that improves both plant nourishment and vitality, bolstering resilience against non-living stressors. It holds the advantage of being environmentally benign and is applicable through soil or foliar methods across various crops [15][16][17]. Furthermore, YE aids in the conversion of insoluble phosphorus to a soluble form, a role noted in [18,19].…”
Section: Introductionmentioning
confidence: 99%